ChemInform Abstract: A Heterogeneous Niobium(V) Oxide Catalyst for the Direct Amidation of Esters. Issue 2 (23rd December 2015) - Ali, Md. Ayub; Siddiki, S. M. A. Hakim; Kon, Kenichi; Shimizu, Ken‐ichi
Abstract: The first example of a heterogeneously catalyzed direct amidation of esters with amines is reported.